MiR‐455‐5p Overexpression Reduces Rat Lung Alveolar Type II Cell Proliferation by Downregulating STRA6. Issue 11 (2nd June 2019) - Zheng, Jintao; He, Qiuming; Tang, Huajian; Xia, Huimin
ABSTRACT: miR‐455‐5p and retinoid signaling pathway and its membrane receptor, STRA6, are associated with lung development. Software copredictions indicate that the miRNA upstream of the STRA6 gene is miR‐455‐5p. We hypothesized that miR‐455‐5p participates in rat lung alveolar Type II cell proliferation by targeting STRA6 and designed this study to investigate the effects of miR‐455‐5p overexpression on rat lung alveolar Type II cells. Dual luciferase reporter gene assay was utilized to confirm the relationship between miR‐455‐5p and STRA6 . An miR‐455‐5p‐expressing adenoviral vector was constructed and transfected into rat lung alveolar Type II cells. STRA6 protein expression was detected in rat lung alveolar Type II cells by Western blotting at 72 hr posttransfection. Retinol concentration was detected by ELISA at 72 hr posttransfection. The cell proliferation was detected by CCK8 assay at 24, 48, and 72 hr posttransfection. Our results showed that STRA6 is a target gene of miR‐455‐5p. STRA6 protein expression was significantly lower in the miR‐455‐5p‐overexpression group than in the NC group (0.615 ± 0.131 vs. 0.958 ± 0.246, P = 0.029). Similar results were observed for retinol concentration (2.985 ± 0.061 vs. 3.949 ± 0.118, P = 0.000). Rat lung alveolar Type II cell proliferation was lower in the miR‐455‐5p‐overexpression group than in the NC group at 24, 48, and 72 hr posttransfection (24 hr: 0.280 ± 0.184 vs. 1.354 ± 0.169 P = 0.026; 48 hr: 0.881 ± 0.016 vs. 1.992 ± 0.050 P = 0.001; 72 hr: 2.105 ± 0.148 vs. 2.937 ± 0.079 P = 0.016). In summary, miR‐455‐5p is associated with lung development. miR‐455‐5p overexpression downregulates STRA6, leading to reduced retinol concentration and rat lung alveolar Type II cell proliferation. Anat Rec, 302:2062–2069, 2019. © 2019 The Authors. The Anatomical Record published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists.